An alternative conformation of the T-cell receptor alpha constant region. - van Boxel, G; Holmes, S; Fugger, L; Jones, E (2010)
Alphabeta T-cell receptors (TcRs) play a central role in cellular immune response. They are members of the Ig superfamily, with extracellular regions of the alpha and beta chains each comprising a V-type domain and a C-type domain. We have determined the ectodomain structure of an alphabeta TcR, which recognizes the autoantigen myelin basic protein. The 2.0-A-resolution structure reveals canonical main-chain conformations for the V(alpha), V(beta), and C(beta) domains, but the C(alpha) domain exhibits a main-chain conformation remarkably different from those previously reported for TcR crystal structures. The global IgC-like fold is maintained, but a piston-like rearrangement between BC and DE beta-turns results in beta-strand slippage. This substantial conformational change may represent a signaling intermediate. Our structure is the first example for the Ig fold of the increasingly recognized concept of "metamorphic proteins."